The level of criminal behavior among women (its causes and effects) from the point of view of the security men (Al-Qardah Police Station/Aqeed)) (Journal of Human Sciences, 2022)
This study aims to identify the level of criminal behavior of women from the point of view of the security men (Al-Qarada Police Station / Sebha Security Directorate) and the reason for choosing it is due to the lack of scientific interest in it. The researcher prepared a tool to collect the necessary information on the subject of the study as a measure of the criminal behavior of women in the light of some variables (gender - educational qualification - job title - marital status - experience - police station). cultural, educational, economic factors, social factors), and the sample consisted of (60) security men, and they were selected in a simple random way. The descriptive analytical approach was used, and the data was analyzed by appropriate statistical methods, and the results of the research resulted in the following: The sample members as a whole can see that the criminal behavior of women within the city of Sabha they have reaches a relatively average level, and there are no statistically significant differences in the criminal behavior of the Women from the point of view of the security men in (personal factors), (economic factors), (cultural and educational factors) and the tool as a whole, and there are differences in the criminal behavior of women from the point of view of the security men in (social factors) according to the gender variable and these differences It was in favor of females, and there were no statistically significant And (economic factors) and there are differences in the criminal behavior of women in (cultural and educational factors), (social factors) and the tool as a whole according to the variable of experience, and these differences are in favor of the security men who have experience (less than 5 years), and there are no significant differences A statistic in the criminal behavior of women from the point of view of the security men according to the variable of the police station. differences in the criminal behavior of women from the point of view of security men according to the educational qualification variable. Also, there are no statistically significant differences in the criminal behavior of women from the point of view of the security men according to the variable of the job title, there are no statistically significant differences in the criminal behavior of women from the point of view of the security men according to the variable of social status, and there are no statistically significant differences in Criminal behavior of women from the point of view of security men in (personal factors)